PP.09.30: DIETARY SALT INTAKE AND RENAL DAMAGE IN PRIMARY ALDOSTERONISM. (June 2015) - Catena, C.; Colussi, G.L.; Nait, F.; Pezzutto, F.; Martinis, F.; Brosolo, G.; Sechi, L.A.
Abstract : Objective: Primary aldosteronism is associated with renal changes that include glomerular hyperfiltration and increased urinary protein excretion that recede after treatment. Although animal studies indicate that dietary salt content is critical for occurrence of aldosterone-related renal damage, there is no evidence of this interaction in patients with primary aldosteronism. The aim of this study was to examine the relevance of dietary salt intake, as assessed by measurement of 24-hour urinary sodium excretion (UNaE), and renal damage in primary aldosteronism before and 1 year after surgical or medical treatment. Design and method: In 46 patients with primary aldosteronism (age 53 ± 12 yr.; 32 males) we measured glomerular filtration rate (GFR) by 24-hour creatinine clearance, and 24-hour urinary sodium (UNaE) and albumin excretion (UAE). Diagnosis of primary aldosteronism was established after screening with the aldosterone-to-renin ratio and subsequent confirmation by a saline load test. Twenty-two patients had bilateral adrenal hyperplasia and 24 adrenal adenoma and were treated with mineralocorticoid receptor antagonists or unilateral adrenalectomy, respectively. Measurements were repeated in all patients one year after treatment. Results: Before treatment, UAE was significantly related with UNaE (r = 0.388; P < 0.01) both in patients with unilateral and bilateral disease. However, when GFR was included in a multivariate regression analysis the relationship between UAE and UNaE was lost. At follow-up and as expected, GFR and UAE declined significantly both in patients treated with mineralocorticoid receptor antagonists and adrenalectomy, whereas UNaE did differ significantly from baseline. Univariate analysis of correlation did not show any relationship of UNaE with UAE in patients treated medically or surgically. Conclusions: In conclusion, dietary salt intake is associated with the extent of subclinical renal damage in primary aldosteronism, but this association is explained by glomerular hyperfiltration and therefore could be attributed to the functional changes occurring in the kidney of these patients.